Menekan Hama dan Menaikan Ekonomi Petani: Pembuatan Pestisida Nabati dari Kulit Bawang - Baraba, Raihana Abdul Aziz; Yendrawati, Reni (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The use of chemical pesticides in agriculture is often a quick and effective way to control pests, but it can have a negative impact on soil fertility and the environment. One of the proposed solutions is the production of plant-based pesticides from natural materials, such as shallot peel, which contain active pest repellents (OPTs). This programme aims to educate farmers in Ngargomulyo village, Tanen hamlet, on the importance of using organic materials and managing soil pH to improve the fertility of their farmland. The activity began with a land survey on 9 August, followed by soil pH testing using a pH meter in several rice fields in the village. The methods used included advice, mentoring and direct application of plant protection products to the farmland. The results of the programme showed that farmers in Tanen Hamlet gained a better understanding of the benefits of organic materials such as shallot skin in protecting crops from pests, as well as the importance of maintaining soil pH balance to remain fertile. In addition, by reducing the use of chemical pesticides, farmers can minimise negative impacts on the soil and the environment and reduce production costs. It is hoped that this programme will encourage farmers to use more natural materials in their farming activities in the future. This program can be developed into commercial product to be sold to other farmers, thereby increasing the added value of waste into products of economic value